Determining the relevance of HLA/KIR matching/mismatching on kidney and liver transplantation rejection: A meta-analysis - Brian Batuan; CRISEL JEAN CAJAYON; BERLINN AIRIANE CASTRO; MIGUEL LUIS AUSTRIA; DERRICK NIKOLAI CO; SOPHIA KRISTINE EBREO; BENJIE CLEMENTE; RAPHAEL ENRIQUE TIONGCO (Nusantara Bioscience, 2021)
Abstract. Batuan B, Cajayon CJ, Castro BA, Austria ML, Co DN, Ebreo SK, Clemente B, Tiongco RE. 2021. Determining the relevance of HLA/KIR matching/mismatching on kidney and liver transplantation rejection: A meta-analysis. Nusantara Bioscience 13: 211-218. The kidney and liver are solid organs commonly transplanted nowadays. However, there are cases wherein graft rejection occurs due to foreign Human Leukocyte Antigen (HLA) proteins. Furthermore, the function of Natural Killer (NK) cells and their receptors in solid organ transplantation is not yet fully elucidated. This study aims to determine the relevance of matching HLA/Killer cell Immunoglobulin-like Receptors (KIR) with kidney and liver transplantation outcomes. First, articles were screened according to the inclusion and exclusion criteria provided, which garnered eight definitive studies. Next, data were tabulated using a standardized extraction form. A meta-analysis was conducted to formulate conclusions regarding the significance of HLA/KIR matching and mismatching in kidney and liver transplantations. Fixed- and random-effects models were utilized to compute and establish 95% CI and pooled ORs wherein a p-value of less than 0.05 is considered significant. A combined Chi-square-based Q test and I2 statistics were used to identify heterogeneity, which was resolved with a funnel plot. In this meta-analysis, only the HLA-Bw4/KIR3DL1 combination was found significant to lower the risk of allograft rejection (OR=0.73; PA=0.009; PH=0.42). Other combinations include HLA-C1 and KIR2DL2/3, HLA-C1 and KIR2DS2/3, HLA-C2 and KIR2DL1/DS2, and HLA-Bw4/KIR3DS1 were found to be insignificant; hence, these do not influence the allograft rejections. In conclusion, the role of HLA/KIR combinations on solid organ transplantation rejection is only significant in HLA-Bw4/KIR3DL1 interaction, which correlates with decreased odds of allograft rejection. Factors including KIR allele variations, insufficient data and journals related to the topic, and unestablished association of HLA/KIR in other organ transplantations affected the results of this meta-analysis; thus, these are recommended to be considered in future studies.